Preparation method and application of core-shell type carbon-based composite anti-corrosion nano electromagnetic wave absorbent

By adopting the preparation method of core-shell carbon-based composite anticorrosion nano electromagnetic wave absorber, the problem that existing electromagnetic wave absorbers are difficult to provide long-term protection in corrosive environments is solved, and the stability of the material in corrosive environments and excellent electromagnetic wave absorbing performance is achieved.

CN119730214APending Publication Date: 2025-03-28CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411797014.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing electromagnetic wave absorbers are difficult to provide long-term protection in corrosive environments, especially iron-based magnetic absorbers are prone to corrosion and deformation in environments such as humidity and heat, coastal salt spray corrosion.

Method used

The preparation method of core-shell carbon-based composite anticorrosion nano electromagnetic wave absorber is adopted. By mixing glucose and sodium stannate hydrated under ultrasonic conditions, hydrothermal reaction is carried out to form a structure with tin dioxide as the core and outer layer as the carbon layer. The carbon layer is chemically inert and enhances the corrosion resistance of the material.

Benefits of technology

It provides long-term protection in corrosive environments, and the material remains stable in wet and heat or salt spray corrosion environments, which can effectively reduce the radar wave reflection response signal and prevent radar from tracking and detecting protected areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730214A_ABST
    Figure CN119730214A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a core-shell type carbon-based composite anti-corrosion nano electromagnetic wave absorbent, the preparation method comprises the following steps: 1, mixing deionized water, glucose and sodium stannate hydrate, and fully stirring under an ultrasonic condition until the system is uniformly mixed to obtain a mixed solution; 2, transferring the mixed solution into a polytetrafluoroethylene reaction lining, and filling the polytetrafluoroethylene reaction lining into a hydrothermal kettle for hydrothermal reaction; 3, after the hydrothermal reaction is finished, cooling to room temperature, centrifuging the reacted hydrothermal product, washing for multiple times, and drying the separated solid-phase material to obtain powder; and 4, calcining the powder obtained in the step 3 in an argon or nitrogen protection environment, naturally cooling, and grinding the product to obtain the core-shell type carbon-based composite anti-corrosion nano electromagnetic wave absorbent. Glucose and sodium stannate are selected as raw materials, the dielectric difference between the carbon material and tin dioxide can induce interface polarization, the dielectric loss effect is further enhanced, and the electromagnetic wave absorbing performance of the material is improved. The electromagnetic wave absorbent is of a structure with stannic oxide as a core and a carbon layer as an outer layer, the carbon layer is not prone to corrosion or erosion, stannic oxide is relatively stable in the natural environment, and therefore the material system has good corrosion resistance and can be used in the damp and hot or salt spray corrosion environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electromagnetic wave absorbers, and in particular to a preparation method and application of a core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber. Background Art

[0002] Electromagnetic wave absorbers can use the electromagnetic effect to convert electromagnetic waves within a certain band into heat dissipation, hinder electrical detection, and play a role in electromagnetic protection. According to the functional mechanism, they can be divided into dielectric and magnetoelectric absorbers. Through composite design, a variety of materials with different dielectric effects are combined to induce interface polarization to improve the performance of electromagnetic wave absorbers.

[0003] CN117625131A mentions a method for preparing a carbon-coated multiferroic electromagnetic absorbing material, wherein nickel ferrite nanoparticles are prepared by a hydrothermal method, and then nickel ferrite is coated with iron nitrate and bismuth nitrate in ethylene glycol and then sintered to prepare bismuth ferrite-coated nickel ferrite nanoparticles, and then bismuth ferrite-coated nickel ferrite nanoparticles are carbon-coated in a buffer solution using a dopamine hydrochloride method, and finally sintered at high temperature. However, iron-based magnetic absorbents often contain some non-stable composition configurations, which are prone to corrosion deformation when used in harsh environments such as damp heat, coastal salt spray corrosion, and oxygen-rich rainwater. Moreover, although a portion of carbon is contained in the composite material system, the proportion of protective carbon in the composite absorbent designed and synthesized by the coating method is relatively low, and the carbon shell is thin, which is difficult to provide long-term protection in a corrosive environment, and corrosion failure will gradually occur with the erosion of the environment. Summary of the invention

[0004] In view of this, the present invention aims to propose a preparation method and application of a core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber to solve the problem that the electromagnetic wave absorber contains a non-stable composition configuration and is difficult to provide long-term protection when used in a corrosive environment.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] On the one hand, the present invention provides a method for preparing a core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber, characterized in that the preparation method comprises the following steps:

[0007] Step 1: Mix deionized water, glucose and hydrated sodium stannate, and stir them thoroughly under ultrasonic conditions until the system is mixed evenly to obtain a mixed solution;

[0008] Step 2: transferring the mixed solution into a polytetrafluoroethylene reaction liner and placing it into a hydrothermal kettle for hydrothermal reaction;

[0009] Step 3: After the hydrothermal reaction is completed and cooled to room temperature, the hydrothermal product after the reaction is centrifuged and washed multiple times, and the separated solid phase material is dried to obtain a powder;

[0010] Step 4: calcine the powder obtained in step 3 under an argon or nitrogen protection environment, grind the product after natural cooling, and obtain a core-shell carbon-based composite anticorrosive nano-electromagnetic wave absorber.

[0011] Furthermore, in step 1, the mass ratio of glucose to hydrated sodium stannate is 1000:9-576.

[0012] Furthermore, in step 2, the reaction temperature of the hydrothermal reaction is 180-190° C., and the reaction time is 3-5 h.

[0013] Furthermore, in step 4, the calcination temperature is 600-1200° C. and the temperature is kept for 2 hours.

[0014] Furthermore, in step 4, during calcination, the heating rate is controlled at 2 to 10° C. / min.

[0015] Furthermore, the prepared core-shell carbon-based composite anti-corrosion nano electromagnetic wave absorber has a structure with tin dioxide as the core and a carbon layer as the outer layer.

[0016] On the other hand, the present invention also proposes the use of the electromagnetic wave absorber prepared by the preparation method of the core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber in coatings.

[0017] Compared with the prior art, the preparation method and application of a core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber described in the present invention have the following advantages:

[0018] (1) Glucose and sodium stannate are selected as raw materials. The dielectric difference between carbon material and tin dioxide can induce interfacial polarization, further enhance the dielectric loss effect, and improve the electromagnetic absorption performance of the material.

[0019] (2) The electromagnetic wave absorber prepared by the present invention has a structure with tin dioxide as the core and a carbon layer as the outer layer, wherein the carbon layer is chemically inert and not easily corroded or eroded. Tin dioxide is also relatively stable in the natural environment. Therefore, the material system has good corrosion resistance and can maintain a stable state in a non-combustion environment, and can be used in a hot and humid or salt spray corrosion environment.

[0020] (3) The electromagnetic wave absorber prepared by the present invention is used as a main filler mixed resin to prepare a corrosion-resistant absorbing coating, which can be applied in a humid atmospheric environment and a marine corrosion application environment, reduce the radar wave reflection response signal of the coated part, and prevent the radar from tracking and detecting the protected area, which has good military significance and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0022] Figure 1 This is a scanning electron microscope image of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 2 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 3 of the present invention;

[0025] Figure 4 This is a scanning electron microscope image of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 4 of the present invention;

[0026] Figure 5 This is a projection electron microscope image of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 3 of the present invention;

[0027] Figure 6 The electromagnetic parameters of the carbon-based composite anticorrosive nano electromagnetic wave absorber prepared in Example 1 of the present invention;

[0028] Figure 7 The electromagnetic parameters of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 2 of the present invention;

[0029] Figure 8 The electromagnetic parameters of the carbon-based composite anticorrosive nano electromagnetic wave absorber prepared in Example 3 of the present invention;

[0030] Fig. 9 The electromagnetic parameters of the carbon-based composite anticorrosive nano electromagnetic wave absorber prepared in Example 4 of the present invention;

[0031] Fig.10 This is a graph showing the electromagnetic loss performance of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 1 of the present invention;

[0032] Fig.11 This is a graph showing the electromagnetic loss performance of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 2 of the present invention;

[0033] Fig.12 This is a graph showing the electromagnetic loss performance of the carbon-based composite anticorrosive nano-electromagnetic wave absorber prepared in Example 3 of the present invention;

[0034] Fig.13This is a graph showing the electromagnetic loss performance of the carbon-based composite anti-corrosion nano-electromagnetic wave absorber prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with specific embodiments. It should be noted that the data in the following experimental examples are obtained by the inventor through a large number of experiments. Due to space limitations, only a part of them is shown in the specification, and those of ordinary skill in the art can understand and implement the present invention under these data. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these changes or modifications also fall within the scope protected by the present application.

[0036] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0037] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0038] The method for preparing a core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber of the present invention comprises the following steps:

[0039] Step 1: Mix deionized water, glucose and hydrated sodium stannate, and stir them thoroughly under ultrasonic conditions until the system is mixed evenly to obtain a mixed solution;

[0040] Step 2: transferring the mixed solution into a polytetrafluoroethylene reaction liner and placing it into a hydrothermal kettle for hydrothermal reaction;

[0041] Step 3: After the hydrothermal reaction is completed and cooled to room temperature, the hydrothermal product after the reaction is centrifuged and washed multiple times, and the separated solid phase material is dried to obtain a powder;

[0042] Step 4: calcine the powder obtained in step 3 under an argon or nitrogen protection environment, grind the product after natural cooling, and obtain a core-shell carbon-based composite anticorrosive nano-electromagnetic wave absorber.

[0043] Specifically, in step 1, the role of adding deionized water is to dissolve glucose and hydrated sodium stannate and provide a liquid phase reaction environment. The amount of deionized water added is sufficient to ensure that all the powders can be dissolved. As a preferred example of the present invention, the mass ratio of glucose to hydrated sodium stannate is 1000:9-576. By controlling the ratio of glucose and sodium stannate in the raw materials to adjust the state of carbon layer wrapping, the synthesis control of composite nano absorbers with different morphologies can be achieved.

[0044] Specifically, in step 2, the volume of the polytetrafluoroethylene reaction liner is selected according to the volume of the added mixed solution, and the selection standard is that the mixed solution can just fill the polytetrafluoroethylene reaction liner and leave a small part of the gap. The reaction temperature of the hydrothermal reaction is 180-190°C, and the reaction time is 3-5h.

[0045] Specifically, in step 4, the calcination temperature is 600-1200° C. and the temperature is kept for 2 hours. More specifically, during calcination, the heating rate is controlled at 2-10° C. / min.

[0046] The preparation of the present invention mainly includes a hydrothermal process, a separation process and a heat treatment process. The hydrothermal process provides reaction conditions to trigger the glycosylation reaction of glucose and sodium stannate under a water-soluble state at a high temperature, and constructs a core-shell structure in which a low-carbon alkyl glucoside layer is coated with tin dioxide. The separation process separates the reaction product and water. The heat treatment process converts the low-carbon alkyl glucoside layer into a carbon layer, improves the degree of carbonization, and the carbon layer wrapped in the outer layer can enhance the overall dielectric loss performance of the material, thereby obtaining a core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber. The present invention adopts a one-step method to obtain an electromagnetic wave absorber with a core-shell structure. Since the reaction process and the required equipment are simple, it has the potential for mass production and batch application.

[0047] The present invention uses glucose and sodium stannate as raw materials. The dielectric difference between the carbon material and tin dioxide can induce interface polarization, further enhance the dielectric loss effect, and improve the electromagnetic absorption performance of the material. The absorbent finally formed is a structure with tin dioxide as the core and the outer layer as the carbon layer, wherein the carbon layer is chemically inert and not easily corroded or eroded. Tin dioxide is also relatively stable in the natural environment. Therefore, the material system has good corrosion resistance, can maintain a stable state in a non-combustion environment, and can be used in a hot and humid or salt spray corrosion environment.

[0048] Example 1

[0049] Mix 120 ml of deionized water, 27 g of glucose, and 0.242 g of hydrated sodium stannate Na2[Sn(OH)6] together, and fully disperse them by ultrasonication using an ultrasonic machine.

[0050] After ultrasound, the mixed solution was transferred into a polytetrafluoroethylene reaction liner, loaded into a hydrothermal kettle, and placed in an oven for hydrothermal reaction at a temperature of 180°C for 4 hours. After the reaction was completed, the mixture was naturally cooled to room temperature.

[0051] The solid-liquid mixture after the hydrothermal reaction was poured out, ethanol was added to the mixture, and the solid phase product in the mixed solution was centrifuged after stirring for 15 minutes. Ethanol was continued to be poured, and the centrifugation step was repeated. The separated solid phase material was dried at 60-80°C for 24 hours until the solid was completely dry and in a brown powder state.

[0052] The obtained brown powder is put into an alumina crucible, placed in a high-temperature tube furnace, and calcined in an argon or nitrogen protection environment at a calcination temperature of 1000°C, a heating rate of 5°C / min, and a heat preservation time of 2 hours. After natural cooling, the product is ground to obtain a carbon-based composite anticorrosive nano-electromagnetic wave absorber.

[0053] Example 2

[0054] Mix 120 mL of deionized water, 27 g of glucose, and 0.968 g of hydrated sodium stannate Na2[Sn(OH)6] together, and fully disperse them using an ultrasonic machine.

[0055] After ultrasound, the mixed solution was transferred into a polytetrafluoroethylene reaction liner, loaded into a hydrothermal kettle, and placed in an oven for hydrothermal reaction at a temperature of 180°C for 4 hours. After the reaction was completed, the mixture was naturally cooled to room temperature.

[0056] The solid-liquid mixture after the hydrothermal reaction was poured out, ethanol was added to the mixture, and the solid phase product in the mixed solution was centrifuged after stirring for 15 minutes. Ethanol was continued to be poured, and the centrifugation step was repeated. The separated solid phase material was dried at 60-80°C for 18 hours until the solid was completely dry and in a brown powder state.

[0057] The obtained brown powder is put into an alumina crucible, placed in a high-temperature tube furnace, and calcined in an argon or nitrogen protection environment at a calcination temperature of 1000°C, a heating rate of 5°C / min, and a heat preservation time of 2 hours. After natural cooling, the product is ground to obtain a carbon-based composite anticorrosive nano-electromagnetic wave absorber.

[0058] Example 3

[0059] Mix 120 mL of deionized water, 27 g of glucose, and 3.872 g of hydrated sodium stannate Na2[Sn(OH)6] together, and fully disperse them using an ultrasonic machine.

[0060] After ultrasound, the mixed solution was transferred into a polytetrafluoroethylene reaction liner, loaded into a hydrothermal kettle, and placed in an oven for hydrothermal reaction at a temperature of 180°C for 4 hours. After the reaction was completed, the mixture was naturally cooled to room temperature.

[0061] The solid-liquid mixture after the hydrothermal reaction was poured out, ethanol was added to the mixture, and the solid phase product in the mixed solution was centrifuged after stirring for 15 minutes. Ethanol was continued to be poured in, and the centrifugation step was repeated. The separated solid phase material was dried at 60-80°C for 20 hours until the solid was completely dry and in a brown powder state.

[0062] The obtained brown powder is put into an alumina crucible, placed in a high-temperature tube furnace, and calcined in an argon or nitrogen protection environment at a calcination temperature of 1000°C, a heating rate of 5°C / min, and a heat preservation time of 2 hours. After natural cooling, the product is ground to obtain a carbon-based composite anticorrosive nano-electromagnetic wave absorber.

[0063] Example 4

[0064] Mix 120 mL of deionized water, 27 g of glucose, and 15.488 g of hydrated sodium stannate Na2[Sn(OH)6] together, and fully disperse them by ultrasonication using an ultrasonic machine.

[0065] After ultrasound, the mixed solution was transferred into a polytetrafluoroethylene reaction liner, loaded into a hydrothermal kettle, and placed in an oven for hydrothermal reaction at a temperature of 180°C for 4 hours. After the reaction was completed, the mixture was naturally cooled to room temperature.

[0066] The solid-liquid mixture after the hydrothermal reaction was poured out, ethanol was added to the mixture, and the solid phase product in the mixed solution was centrifuged after stirring for 15 minutes. Ethanol was continued to be poured in, and the centrifugation step was repeated. The separated solid phase material was dried at 60-80°C for 20 hours until the solid was completely dry and in a brown powder state.

[0067] The obtained brown powder is put into an alumina crucible, placed in a high-temperature tube furnace, and calcined in an argon or nitrogen protection environment at a calcination temperature of 1000°C, a heating rate of 5°C / min, and a heat preservation time of 2 hours. After natural cooling, the product is ground to obtain a carbon-based composite anticorrosive nano-electromagnetic wave absorber.

[0068] The scanning electron microscope images of the samples prepared in Examples 1 to 4 are as follows: Figures 1 to 4 As shown. Under the regulation of different addition ratios of glucose and sodium stannate, the prepared electromagnetic wave absorbers showed different particle sizes and microscopic morphologies, but the overall structure was a spherical structure in a core-shell state. With tin dioxide as the core, low-carbon alkyl glucoside grows on the outside to form a core-shell structure. After heat treatment, the glucoside is deoxygenated and converted into a carbon layer, eventually forming a core-shell carbon-based composite material. Compared with other morphologies such as flakes, the nano-sized core-shell structure can be better and more evenly dispersed in the coating, and has stable properties. The parameters of electromagnetic wave absorbers produced in different batches are consistent, reducing the adverse effects of differentiation on the coating.

[0069] When the amount of glucose remains unchanged and the amount of sodium stannate added is doubled, the amount of tin dioxide that can be produced as a core increases significantly, and the size of the glycoside-encapsulated oxidized nanoparticles generated by the glycosylation reaction gradually decreases. In Example 1, the size of the nanoparticles synthesized with a low amount of sodium stannate added is about 200nm. In Examples 2 to 4, as the sodium stannate content increases, the synthesized nanoparticles gradually shrink. Taking Example 3 as an example, Figure 5The transmission electron microscope image of the sample prepared in Example 3 is shown in FIG. The size of the nanoparticles prepared under the addition ratio of Example 3 is about 150 nm, wherein the diameter of the tin dioxide core is 75 nm, accounting for 1 / 4 of the total volume, and has a thick carbon layer. The stable tin dioxide wrapped in the thick carbon layer is not easily corroded by the corrosive environment and can maintain good electromagnetic absorption performance in extreme environments.

[0070] The electromagnetic wave absorber of the present invention uses stannate as the main tin source, and the stannate can also be replaced by other substate metal salts to participate in the glycosidation reaction of glucose to obtain the corresponding carbon-wrapped metal oxide core-shell material.

[0071] The samples prepared in Examples 1 to 4 were mixed with paraffin wax at a ratio of 10:90 and pressed into rings with an inner diameter of 3.04 mm and an outer diameter of 7.00 mm. Electromagnetic parameter tests were performed using a vector network analyzer, and reflection loss performance parameters were calculated. The results are as follows: Figures 6 to 9 As shown. Through vector network analyzer test and calculation, in the frequency range of 2 to 18 GHz, the real part of the dielectric of the sample in Example 1 is 8.9 to 5.7, the imaginary part of the dielectric is 5.1 to 2.5, the real part of the magnetic permeability approaches 1.0, and the imaginary part of the magnetic permeability approaches 0; the real part of the dielectric of the sample in Example 2 is 10.8 to 6.3, the imaginary part of the dielectric is 7.9 to 2.9, the real part of the magnetic permeability approaches 1.0, and the imaginary part of the magnetic permeability approaches 0; the real part of the dielectric of the sample in Example 3 is 11.7 to 5.6, the imaginary part of the dielectric is 6.3 to 3.1, the real part of the magnetic permeability approaches 1.0, and the imaginary part of the magnetic permeability approaches 0; the real part of the dielectric of the sample in Example 4 is 8.4 to 5.1, the imaginary part of the dielectric is 3.4 to 2.1, the real part of the magnetic permeability approaches 1.0, and the imaginary part of the magnetic permeability approaches 0.

[0072] The overall values ​​of the electromagnetic parameters of the samples of Examples 1 to 4 fluctuate slightly, which is due to the difference in the raw material ratio causing the change in the overall tin-carbon ratio. Under the raw material ratio of the present application, the impedance matching and attenuation performance of the prepared absorbent can achieve a good balance, giving the absorbent excellent electromagnetic wave absorption ability.

[0073] The electromagnetic wave composite absorbers prepared in Examples 1 to 4 were prepared into coatings, and the electromagnetic loss performance of the coatings at different coating thicknesses was investigated. The specific results are as follows: Figures 10 to 13 As shown, the absorbent prepared by the method of the present invention has certain electromagnetic absorption performance when used as coating. Figures 10 to 13The area within the range of the two black lines is the range of electromagnetic absorption capacity corresponding to the reflectivity of the coating lower than -10dB and the corresponding electromagnetic reflection efficiency of 90%. Within this region, the effective absorption bandwidth of the coating corresponding to Examples 1 to 4 is all at 6GHz. When the coating thickness is 2mm, the main frequency range for electromagnetic waves is 12 to 18GHz. The electromagnetic absorption performance mainly comes from the intrinsic dielectric loss of carbon materials and tin dioxide, and the interface polarization effect caused by the difference in dielectric parameters between the two. When electromagnetic waves are incident on the material, they are converted into heat energy dissipation under the action of dielectric response. Limited by its own characteristics, its loss effect on electromagnetic waves is better in the medium and high frequency bands of 12 to 18GHz. Among them, the maximum effective absorption bandwidth of Example 1 reaches 6.16GHz, corresponding to a thickness of 2.2mm. The maximum effective absorption bandwidth of Example 2 reaches 6.00GHz, the maximum effective absorption bandwidth of Example 3 reaches 5.84GHz, and the maximum effective absorption bandwidth of Example 4 reaches 5.20GHz. In view of the fact that the use of electromagnetic wave absorbers to prepare coatings is a prior art, it will not be described in detail here.

[0074] The present invention discloses a method for preparing a core-shell carbon-based composite anticorrosive nano-electromagnetic wave absorber. By adjusting the ratio of raw materials involved in the reaction and utilizing the growth process and volume change of the reactants during the reaction, the morphology and dispersion state of the composite anticorrosive nano-electromagnetic wave absorber in different coating states can be controlled, thereby adjusting electromagnetic parameters and obtaining better electromagnetic wave absorption performance.

[0075] The electromagnetic wave absorber prepared by the present invention has excellent electromagnetic wave absorbing performance, and the carbon layer wrapping the nano metal oxide can effectively block the corrosive medium. It is used as a main filler mixed with resin to make corrosion-resistant absorbing coatings, which can be applied in humid atmospheric environments and marine corrosion application environments, reduce radar wave reflection response signals of the coated parts, and prevent radar tracking and detection of the protected areas, which has good military significance and social benefits.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a core-shell carbon-based composite anticorrosive nano-electromagnetic wave absorber, characterized in that: The preparation method comprises the following steps: Step 1: Mix deionized water, glucose and hydrated sodium stannate, and stir them thoroughly under ultrasonic conditions until the system is mixed evenly to obtain a mixed solution; Step 2: transferring the mixed solution into a polytetrafluoroethylene reaction liner and placing it into a hydrothermal kettle for hydrothermal reaction; Step 3: After the hydrothermal reaction is completed and cooled to room temperature, the hydrothermal product after the reaction is centrifuged and washed multiple times, and the separated solid phase material is dried to obtain a powder; Step 4: calcine the powder obtained in step 3 under an argon or nitrogen protection environment, grind the product after natural cooling, and obtain a core-shell carbon-based composite anticorrosive nano-electromagnetic wave absorber.

2. The method for preparing the core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber according to claim 1, characterized in that: In step 1, the mass ratio of glucose to hydrated sodium stannate is 1000:9-576.

3. The method for preparing the core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber according to claim 1, characterized in that: In step 2, the reaction temperature of the hydrothermal reaction is 180-190° C., and the reaction time is 3-5 h.

4. The method for preparing the core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber according to claim 1, characterized in that: In step 4, the calcination temperature is 600-1200°C and the temperature is kept for 2 hours.

5. The method for preparing the core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber according to claim 1, characterized in that: In step 4, during calcination, the heating rate is controlled at 2 to 10°C / min.

6. The method for preparing the core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber according to claim 1, characterized in that: The prepared core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber has a structure with tin dioxide as the core and a carbon layer as the outer layer.

7. Use of an electromagnetic wave absorber prepared by the method for preparing a core-shell carbon-based composite anticorrosive nano electromagnetic wave absorber as claimed in any one of claims 1 to 6 in coatings.